Predictive Failure Detection in Enterprise Data Pipelines Using Machine Learning and Data Observability Metrics - Shashank Akinapalli (International Journal of Intelligent Systems and Applications in Engineering, 2026)
Enterprise data pipelines serve as the backbone of modern analytics, business intelligence, and data-driven decision-making systems. As organizations increasingly rely on real-time and large-scale data processing, pipeline failures can result in delayed insights, data inconsistencies, operational disruptions, and significant financial losses. Traditional monitoring approaches primarily focus on reactive detection mechanisms, identifying issues only after failures occur. Recent advancements in Data Observability and Machine Learning have enabled organizations to move toward proactive failure prediction and prevention. This research proposes a Predictive Failure Detection Framework that integrates machine learning techniques with data observability metrics to identify potential failures before they impact business operations. The framework continuously analyzes operational indicators such as pipeline latency, data freshness, schema changes, throughput, error rates, and resource utilization to predict anomalies and failure events. Experimental evaluation demonstrates that predictive analytics significantly improves failure detection accuracy, reduces downtime, and enhances pipeline reliability. The proposed framework contributes to the development of intelligent, resilient, and self-monitoring data engineering ecosystems.